New therapy, new challenges: The effects of long-term continuous flow left ventricular assist device on inflammation. (15th July 2016) - Grosman-Rimon, Liza; Billia, Filio; Fuks, Avi; Jacobs, Ira; A. McDonald, Michael; Cherney, David Z.; Rao, Vivek
Abstract: Surgically implanted continuous flow left ventricular assist devices (CF-LVADs) are currently used in patients with end-stage heart failure (HF). However, CF-LVAD therapy introduces a new set of complications and adverse events in these patients. Major adverse events with the CF-LVAD include right heart failure, vascular dysfunction, stroke, hepatic failure, and multi-organ failure, complications that may have inflammation as a common etiology. Our aim was to review the current evidence showing a relationship between these adverse events and elevated levels of inflammatory biomarkers in CF-LVAD recipients. Highlights: Inflammation is elevated in patients with CF-LVAD support. Inflammation may have detrimental effects on CF-LVAD recipients. Future studies should examine strategies to reduce inflammation.